THE IMPACT OF TOLL ROAD CONSTRUCTION ON CHANGES IN BUILT-UP LAND (CASE STUDY OF TRANS JAVA TOLL ROAD) - Fakhruddin, Ahmad; Gultom, Yohanna M.L. (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2021)
This study aims to see the impact of toll road construction of the Trans Java toll road on changes in a built-up land. The data processing and analysis in this study uses a difference-in-difference approach to see the impact before and after the construction of the toll road. This study uses district/city administrative boundaries as the unit of analysis and 92 regencies or cities. The selection of locations that are the focus of the research is based on the regency/cities through which the toll road passes as well as those bordering the regency/cities through which the toll roads pass.. The results of data processing and analysis show that there is an increase in the area of built-up land by 7% when compared to regency/cities that are not passed by toll roads. From a policy perspective, the construction of the Trans Java toll road can be said to have a positive impact on the built up land. That is, the closer to access, the more economic activity and growth of built up land